2010
DOI: 10.4061/2010/546593
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Physical Activity and Bone during Adolescence Differs according to Sex and Biological Maturity

Abstract: This study examines the relationships between bone mass, physical activity, and maturational status in healthy adolescent boys and girls. Methods. Ninety-nine early high-school (Year 9) students were recruited. Physical activity and other lifestyle habits were recorded via questionnaire. Anthropometrics, muscle power, calcaneal broadband ultrasound attenuation (BUA), bone mineral content (BMC), and lean tissue mass were measured. Maturity was determined by Tanner stage and estimated age of peak height velocity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…However, it is possible that BMD among women depends more on variable accrual of peak bone mass during adolescence, and that these effects overwhelm the relatively smaller longitudinal physical activity effects. A recent study among adolescents demonstrated that the relationship between risk factors and BMD depends on sex, and in particular that PA was a more important predictor of BMD in adolescent boys than in adolescent girls [29]. The sexual dimorphism in bone acquisition is related to endocrine regulators, with testosterone and estrogen having different effects on acquisition of lean mass, fat mass, and bone.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that BMD among women depends more on variable accrual of peak bone mass during adolescence, and that these effects overwhelm the relatively smaller longitudinal physical activity effects. A recent study among adolescents demonstrated that the relationship between risk factors and BMD depends on sex, and in particular that PA was a more important predictor of BMD in adolescent boys than in adolescent girls [29]. The sexual dimorphism in bone acquisition is related to endocrine regulators, with testosterone and estrogen having different effects on acquisition of lean mass, fat mass, and bone.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is possible that the environmental determinants of bone development during adolescence differ according to sex as was previously described for the relationship between physical activity and BMD (54) . In order to optimize feasibility and to minimize radiation exposure we used forearm BMD measured by DXA.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reported relationship of physical activity and bone to maturity [21], examination of exercise effects in older children was warranted. The POWER PE trial [8] was designed to specifically target peripubertal adolescents.…”
Section: Discussionmentioning
confidence: 99%